Development of automation power factor correction system by using pic microcontroller through simulation study - Atifa Faaidha Munauwer (School of Electrical System Engineering, Universiti Malaysia Perlis, 2015)
This thesis presents the design and analysis of an automatic power factor correction system using PIC microcontroller for single phase low voltage distribution system (230V/50Hz). Power factor plays a great role in an electrical system.